Longitudinal muscle shows abnormal relaxation responses to nitric oxide and contains altered levels of NOS1 and elastin in uncomplicated diverticular disease - Mark Golder; David Burleigh; Lucy Ghali; Roger M. Feakins; Peter J. Lunniss; Nicholas Williams; Harshad Navsaria (2007)
Abstract Objective Recent evidence challenges the ‘low‐fibre/high‐colonic intraluminal pressure’ hypothesis of diverticular disease (DD) and raises the possibility that other mechanisms are involved. Although bowel wall smooth muscle is known to be hypercontractile in DD, the nature of its relaxation is unknown. The present study investigated colonic smooth muscle responses to nitric oxide, as well as the smooth muscle contents of neural nitric oxide and elastin associated with the disease. Method Immunohistochemical/image analysis of antibodies to nitric oxide synthase (NOS1), co‐localized with protein gene product (PGP) and to elastin, was performed on three histological sections of sigmoid colons from 20 patients (10 DD, 10 controls) following resections for rectal tumours. Organ bath experiments examined smooth muscle responsiveness to nitroprusside, a nitric oxide donor. Results Uncomplicated diverticular longitudinal muscle showed lower nitric oxide immunoreactivity compared with controls: median percentage surface area of NOS1 over PGP was 26.0% (range 0.5–58.3), controls 45.0% (35.0–70.1; P = 0.018). Median percentage surface area of elastin was elevated, 21.3% (10.6–45.6), controls 8.2% (1.7–13.5; P = 0.0002), together with a low sensitivity to nitroprusside [mean − log EC 50 5.3 (SD 0.5), controls 6.6 (SD 0.5), difference 1.3, 95% CI 0.8–1.7; P < 0.0001] and there were lower maximum relaxation responses to nitroprusside compared with controls: median percentage (relaxation induced by nitroprussside/contraction induced by bethanecol) was 52.0%, range (20.0–92.0), controls 100.0% (71.0–125.0), P < 0.0001. No statistically significant differences were found in circular muscle, at the sample size studied. Conclusion This study established, for the first time, specific abnormalities in longitudinal muscle relaxation and contents of neural nitric oxide and elastin in uncomplicated DD. These findings may have important implications for both colon structure and function in the disease.